Immune features and clinical characteristics of chikungunya fever in children: differences from adults and across pediatric age groups - Yilin Li; Shunhang Wen; Hailin Zhang (Frontiers in Pediatrics, 2026)
Chikungunya fever (CHIKF) is an acute infectious disease transmitted by Aedes mosquitoes, with primary symptoms including fever, rash and joint pain. The immune features and clinical manifestations of CHIKF in children differ from those observed in adults. Following chikungunya virus (CHIKV) infection, children more frequently present with high fever, rash, and neurological complications compared with adults, whereas arthralgia and chronic manifestations are less commonly observed. Clinical features also vary among pediatric age groups. This review summarizes current evidence on the age-related immunological and clinical characteristics of CHIKV infection and highlights their implications for pediatric disease management.